Clinical outcomes of 154 hand-assisted laparoscopic surgeries for left sided colon and rectal cancer: single center experience - Dulskas, Audrius; Samalavičius, Narimantas Evaldas; Gupta, Rakesh Kumar; Kazanavičius, Darius; Petrulis, Kęstutis; Lunevičius, Raimundas (Lietuvos chirurgija, 2013)
Background / objective HALS technique has provided all the benefits of a minimal invasive surgery, is a safe and effective procedure. Our study was aimed to describe characteristics of patients admitted to Institute of Oncology, Vilnius University due to left sided colon and rectal cancer for hand-assisted laparoscopic surgery (HALS), colorectal resections performed, intraoperative, postoperative, incision and trocar site long-term clinical outcomes. Laparoscopic colectomy is avoided because of its technical difficulty, steep learning curve, and increased operative times. Hand-assisted laparoscopic colectomy is an alternative technique that addresses these problems while preserving the short-term benefits of laparoscopic colectomy. Our study was aimed to describe characteristics of patients admitted due to left sided colon and rectal cancer for hand-assisted laparoscopic surgery (HALS), colorectal resections performed, intraoperative, postoperative, incision and trocar site long-term clinical outcomes. Methods A prospectively maintained database was used to identify all patients who underwent HALS for left sided colon and rectal cancer at the Institute of Oncology, Vilnius University, from July 1, 2009, when HALS using transumbilical handport incision was started, to October 1, 2013. Results 154 HALS colorectal resections were performed. The patients’ mean age was 63±11 years. There were 79 male and 75 female patients. BMI was 27.3 ± 5.8 kg/m2. Forty-four patients (28.5%) have experienced a prior abdominal surgery. The mean HALS time is 105 minutes (55–185). Conversion rate was 3.2% (5/154). The average number of lymph nodes harvested was 15 (3–49). The median of return of gastrointestinal function was 2.5 days (2.2–4.5). The median length of hospital stay was 6.8days (3 – 31). Postoperative complication rate was 9.7%. Two patients (1.3%) demanded explorative laparotomy. Postoperative mortality rate was 0.65%. There were 4 (2.6%) incisional hernias seen on a mean follow-up of 7.0±3.4 months. Conclusions HALS technique has provided all the benefits of a minimal invasive surgery. HALS colorectal resection is a safe and effective procedure. Keywords: Hand assisted laparoscopic surgery (HALS); Laparoscopic colectomy; Outcomes. Ranka asistuojamų 154 laparoskopinių kolektomijų dėl kairės pusės storosios ir tiesiosios žarnos vėžio rezultatai: vieno centro patirtis Įvadas/ tikslas HALS technika apima visus minimaliai invazyvios chirurgijos privalumus, yra saugi ir efektyvi. Šioje studijoje prospektyviai nagrinėjama pacientų, kuriems dėl kairės pusės storosios ar tiesiosios žarnos vėžio Vilniaus universiteto Onkologijos institute buvo atlikta ranka asistuojama laparoskopinė kolektomija (HALS), demografiniai rodikliai, procedūros pobūdis, intraoperaciniai ir pooperaciniai duomenys. Pasaulyje kas dešimta kolektomija atliekama laparoskopiškai. Laparoskopija nėra dažna dėl techninių sunkumų, ilgos mokymosi kreivės, ilgesnės operacijos trukmės. Ranka asistuojama laparoskopinė kolektomija minėtų trūkumų neturi. Ligoniai ir metodai Prospektyviai buvo išanalizuotas 154 pacientas, kuriam 2009 07 01 – 2013 10 01 metais Vilniaus universiteto Onkologijos institute buvo atlikta HALS operacija dėl kairės pusės storosios ar tiesiosos žarnos vėžio. Rezultatai Atlikta 154 HALS kolorektalinės rezekcijos. Pacientų amžius – 63±11 metai. Operuota 79 vyrai ir 75 moterys. KMI buvo 27,3 ± 5,8 kg/m2. 44 pacientams (28,6 %), anamnezės duomenimis, buvo atliktos pilvo operacijos. Vidutinė operacijos trukmė – 105 minutės (55–185). Konversijų dažnis – 3,2 % (5/154). Vidutinis pašalintų limfmazgių skaičius buvo 15 (3–49). Gastrointestinė funkcija atsitaisė per 2,5 dienos (2,2–4,5). Pooperacinio periodo trukmė – 6,8 dienos (3–31). 9,7 % atvejų pasitaikė komplikacijų. Dviem pacientams (1,3 %) atlikta relaparotomija. Pooperacinio mirtingumo dažnis buvo 0,65 %. Keturiems pacientams (2,6 %) diagnozuotos pooperacinės išvaržos (stebėjimo vidurkis 7,0±3,4 mėn.). Išvados HALS technika apima visus minimaliai invazyvios chirurgijos privalumus, yra saugi ir efektyvi. Reikšminiai žodžiai: Ranka asistuojama laparoskopinė chirurgija (HALS), laparoskopinė kolektomija, baigtys.